تأثير البيانات المحاسبية المنشورة على القيمة السوقية لأسهم شركات التأمين بالمملكة العربية السعودية - يوسف، عبدالله إبراهيم عثمان; العجب، سالم العجب سالم (جامعة عدن - كلية العلوم الإدارية, 2013)
This study aimed to identify whether there is a relationship between published accounting data in financial statements and performance measures derived from them, and the share market values of of Cooperative Insurance Companies in Saudi Arabia to measure the ability of the investors in this sector to use the accounting data when they made a decision to invest in the shares of these companies, in order to examine the hypothesized relationship the study covered 31 companies from the listed insurance companies in Saudi financial market equivalent percentage (88.6%) of the research community During the period from 2011 to 2012. Analysis of multiple regression linear models of the study showed lack statistically significant relationship between share market value of Cooperative Insurance Companies in Saudi Arabia as depended variable and performance measures derived from income and financial position statements, company size as independent variables, and there is no statistically significant relationship between share market valueand marketratios except net operating cash flows per share, while Pearson correlation coefficients showednegative significant correlation between share market value andequity ratio, as well as apositive significant correlation between share market value and debt to equity ratio, therefore these relationships are not consistent with the normal expectation. These results confirm that the shares prices of cooperative insurance companies in Saudi Arabia are not frequently associated with accounting data Listed in published financial statements, which shows that the investor in this sector does not have Sufficient knowledge to analyze accounting data and make investment decisions based on the results of the analysis, butthey depend on the other factors. Based on these findings the study concluded with several recommendations, the most important is need to perceive investors to in cooperative insurance sector to the importance of published financial reports, and performance measures derived from them, because of their importance in valuation company financial situations and thus be used to predict the share market value
هدفت هذه الدراسة إلى التعرف على مدى وجود علاقة بين البيانات المحاسبية المنشورة بالقوائم المالية ومقاييس الأداء المشتقة منها والقيمة السوقية لأسهم شركات التامين التعاوني بالمملكة العربية السعودية لقياس مقدرة المستثمر في هذا القطاع على استخدام البيانات المحاسبية عند اتخاذه قرار الاستثمار في أسهم تلك الشركات، ولفحص العلاقة المفترضة غطت الدراسة (31) شركة من شركات التأمين المدرجة بالسوق المالية السعودية تعادل نسبة (88.6%) من مجتمع البحث خلال الفترة من 2011م إلى2012م. بتحليل نماذج الانحدار الخطي المتعدد للدراسة تم التوصل إلى عدم وجود علاقة ذات دلالة إحصائية بين القيمة السوقية لأسهم شركات التأمين التعاوني بالمملكة العربية السعودية كمتغير تابع ومقاييس الأداء المشتقة من قائمتي الدخل والمركز المالي وحجم الشركة كمتغيرات مستقلة، كما لا توجد علاقة ذات دلالة إحصائية بين القيمة السوقية للسهم والنسب السوقية باستثناء نصيب السهم من التدفقات النقدية التشغيلية، بينما اظهر معامل ارتباط بيرسون وجود ارتباط سالب ذي دلالة إحصائية بين القيمة السوقية للسهم ونسبة الملكية وارتباط إيجابي ذي دلالة إحصائية بين القيمة السوقية للسهم ونسبة المديونية وهذه العلاقات لا تتفق مع التوقع الطبيعي. تؤكد هذه النتائج أن أسعار أسهم شركات التأمين التعاوني بالمملكة العربية السعودية لا ترتبط كثيرا بالبيانات المحاسبية الواردة بالقوائم المالية المنشورة، مما يدل على أن المستثمر في هذا القطاع ليس لديه الدراية الكافية بتحليل البيانات المحاسبية واتخاذ قرارات الاستثمار بناءا على نتائج التحليل وإنما يعتمد في ذلك على عوامل أخرى. بناءا على تلك النتائج ختمت الدراسة بعدة بتوصيات أهمها ضرورة توعية المستثمرين في قطاع التامين التعاوني بأهمية التقارير المالية المنشورة ومقاييس الأداء المشتقة منها لما لها من أهمية في تقييم الوضع المالي للشركة وبالتالي استخدامها في التنبؤ بالقيمة السوقية للسهم
Keywords: السعودية -- شركات التأمين -- التأمين التعاوني -- القوائم المالية -- البيانات المحاسبية